2020
DOI: 10.1002/adsc.202000660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycyclic Furan and Chromene Derivatives via Cascade Reactions Enabled by Cleavage of Multiple C(sp3)−F Bonds

Abstract: The strong and unreactive CÀ F bond makes polyfluorocarbons extremely long-lived and potentially toxic. A successive selective and controllable C(sp 3)À F functionalization of polyfluoroalkylated ketones with Sand O-nucleophiles to enable efficient synthesis of pharmaceutically important fluorine-and sulfurcontaining polycyclic furan and chromene derivatives under transition metal-free conditions is demonstrated here. The combination of CÀ S/CÀ O coupling, aromatization, and cyclization cascade contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 71 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…On the basis of these obtained results, a proposed mechanism is outlined in Scheme . Initially, a successive defluorination of perfluoroalkyl substrate 1 under the effect of the alkali-metal base gives unstable naphthalen-1­(4 H )-one intermediate B , which further undergoes the condensation with benzamidine 2 to afford the imine species C . The following intramolecular defluorinative amination of resultant intermediate C through 7- endo-trig cyclization furnishes the ring-closure product E .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of these obtained results, a proposed mechanism is outlined in Scheme . Initially, a successive defluorination of perfluoroalkyl substrate 1 under the effect of the alkali-metal base gives unstable naphthalen-1­(4 H )-one intermediate B , which further undergoes the condensation with benzamidine 2 to afford the imine species C . The following intramolecular defluorinative amination of resultant intermediate C through 7- endo-trig cyclization furnishes the ring-closure product E .…”
Section: Resultsmentioning
confidence: 99%
“…The existence of TBAB might contribute to autoaromatization. It is possible that the TBAB additive would accelerate both events of intermolecular condensation reaction and intramolecular C–N formations, but the detailed mode of this action remained elusive. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the control experiments without any catalyst (entry 14) showed that catalyst was not crucial in this reaction. To our delight, the reaction would be significantly promoted when a series of bases were added (entries [15][16][17][18][19][20][21][22][23], and the screening of bases showed that Na 2 CO 3 was the best. Thus, the optimal reaction conditions were summarized in entry 15, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, owing to the pursuit of economy and ecofriendliness, alkali-catalyzed reactions, especially alkali metal carbonates, have become more and more popular. [16] Shen and co-workers [17] developed a highly selective functionalized C(sp 3 )-F bond formation strategy by efficient combination of TBAB (tetra-n-butylammonium bromide) and Cs 2 CO 3 . Shi [18] disclosed the cascade dimerization and cyclization of 2-sulfoaminoacrylate derivatives catalyzed by the inorganic base K 2 CO 3 to synthesize dihydro-2-oxopyrrole (DPO) derivatives in one step.…”
Section: Introductionmentioning
confidence: 99%